Birthplace Diversity and Economic Growth: Evidence from the US States in the Post-World War II Period - Frédéric Docquier; Riccardo Turati; Jérôme Valette; Chrysovalantis Vasilakis (Fondation pour les études et recherches sur le développement international (FERDI), 2018)
This paper empirically revisits the impact of birthplace diversity on economic growth. We use panel data on US states over the 1960-2010 period. This rich data set allows us to better deal with endogeneity issues and to conduct a large set of robustness checks. Our results suggest that diversity among college-educated immigrants positively affects economic growth. We provide converging evidence pointing at the existence of skill complementarities between workers trained in different countries. These synergies result in better labor market outcomes for native workers and in higher productivity in the R&D sector. The gains from diversity are maximized when immigrants originate from economically or culturally distant countries (but not both), and when they acquired part of their secondary education abroad and their college education in the US. Overall, a 10% increase in high-skilled diversity raises GDP per capita by about 6%. On the contrary, low-skilled diversity has insignificant effects.
Keywords: F22; J61; 330; Immigration; Culture; Birthplace Diversity; growth